Germination test as a fast method to detect glyphosate-resistant sourgrass - Dias,Marcos Altomani Neves (2015)
The occurrence of weed species with different levels of resistance to glyphosate has increasingly spread in agricultural areas. In Brazil, sourgrass is among the main species presenting issues in this regard. Thus, fast and reliable methods to detect glyphosate resistance are of special interest for this specie, either for research or rational management purposes. This study was carried out to verify the feasibility of using the germination test to detect glyphosate resistance in sourgrass. The experiment was conducted with two sourgrass biotypes, with different levels of susceptibility to glyphosate. The seeds were previously imbibed in solutions composed of 0, 0.1875%, 0.25%, 0.75%, 1.5%, 3% and 6% of glyphosate during two periods, five and ten minutes, and submitted to germination tests. The results indicate the germination test as a feasible and time-saving approach to evaluate glyphosate-resistant sourgrass, with results available in seven days.